Access to, Use, and Effect of Open Educational Resources: The Perspectives of LIS Academics in Selected Nigerian Universities - Olufemi Peter Owoeye; Adeyinka TELLA; Aderinola Ololade Dunmade (Universitas Sebelas Maret, 2024)
This study investigated access to, use of, and the effect of Open Educational Resources (OER) on LIS academics in Nigeria. The study adopted a purely quantitative method, using a survey as the research design. The population of the study comprised LIS academic staff in Nigerian universities. Through a total enumeration method, a sample of 140 LIS academics from 15 universities in Nigeria was selected. A questionnaire developed for data collection was administered to the 140 respondents, of which 133 copies were returned. Seven objectives were developed to guide the study. The results demonstrated that office documents such as Word and PowerPoint, open textbooks, lecture notes, quizzes and tutorials, MOOCs, learning modules, and open courseware are the OER resources most frequently accessed by LIS academics. Mobile phones and laptop computers are the primary devices used by LIS academics for accessing OER. OER are used by LIS academics for teaching and learning, research, preparation for workshops, seminars, conference presentations, and class notes. The effects of OER on LIS academics include the ability to use materials created by other colleagues and customise course materials to create an ideal course packet or textbook. Policies guiding the use of OER include equal access, protection of intellectual property rights, and open licences such as Creative Commons. The challenges LIS academics encounter when using OER include frequent power outages, untimely updates of OER repositories, and prolonged periods spent searching for resources in institutional repositories.